Smart Village Initiatives: Bridging the Urban-Rural Divide Through Digital Inclusion - Ridzki, Mohamad Maulana (Journal of Village Development Innovation, 2024)
This study examines the role of smart village initiatives in addressing the digital divide between urban and rural areas, focusing on digital inclusion's potential to drive socioeconomic development. The objective is to evaluate how these initiatives contribute to economic growth, educational improvement, and local employment. Using a qualitative research approach, data were gathered through interviews and focus group discussions with community leaders, residents, and program facilitators. Findings reveal that digital inclusion has increased rural income by enhancing market access, supported e-learning initiatives to improve educational outcomes, and created new job opportunities through digital literacy training. However, implementation challenges were observed, such as limited connectivity and digital literacy gaps. These results suggest that while smart village initiatives hold significant potential, successful implementation requires ongoing investment and stakeholder collaboration. The study provides practical insights for policymakers to promote sustainable development in rural areas.